Psychological Conditions for the Acceptance of Religious Education by a New Generation of Russians - Tatiana N. Knyazeva; Lidiya E. Semenova; Anna V. Chevachina; Marina B. Batyuta; Elena V. Sidorina (International Review of Management and Marketing, 2016)
The relevance of the problems stated in the article is determined by fundamental changes in the entire Russian society, which affected its foundations and traditional values. Amidst weakening of regulative influence of religion over various aspects of social life in the late twentieth century, the level of religiosity of the citizens, including youth, significantly increased. In this connection, this article aims to identify the nature of religiosity of Russian youth and the specifics of relationship of religiosity with pragmatic life goals. The leading method to study this problem is problem-oriented interviews, allowing to reveal the attitude of modern Russian youth towards religion under the conditions of new social realities. The article reveals that among the Russian youth there is a predominance of those who do not consider themselves to be true believers, who express doubts about the existence of true believers, who demonstrate some skepticism as regards religiosity of their contemporaries and explain the appeal towards religion by ignorance, fashion and human influence of significant others. At the same time, along with their peers, claiming to be true believers, they tend to view religion as a means of consolation and support, attributing to it the function of protection and not that of moral perfection and spiritual renewal. The article also provides the facts, manifistating the presence among true youth believers of egoistic religious motivation and relationship to God from the standpoint of personal well-being, which suggests its pseudo-religiosity. Materials of the article are of practical value for the use of this information for educational purposes and in educational courses with religious content.